Regulating artificial intelligence and child sexual abuse in the European Union: “The role of artificial intelligence in combating sexual exploitation of minors – a disaster or a tool for fighting crime” - France, Patrīcija (Riga Graduate School of Law, 2024)
Over the years, artificial intelligence has been developing rapidly, allowing its users to generate all types of material, benefiting the user. However, with great technology comes great risk. One of these risks is deepfakes – generated or manipulated content e.g. image, audio, video that resembles existing persons, objects or other entities and would falsely appear to be truthful. This technology has created proliferation of a new phenomenon – deepfake child sexual abuse material, which poses a significant challenge for regulation and law enforcement – violation of the General Data Protection Regulation, number of difficulties investigating deepfake child sexual abuse material, increased usage of the “darknet”. Currently, the European Union Artificial Intelligence Act has been passed which may regulate this issue, however, there may be 11 other legal frameworks that may be applicable.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Criminal law; Artificial intelligence; deepfake; sexual abuse; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; General Data Protection Regulation